2018
DOI: 10.3892/ol.2018.9515
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of plasma mitochondrial DNA content in patients with lung cancer

Abstract: Alterations of mitochondrial DNA (mtDNA) have been identified in several types of solid tumor. However, to the best of our knowledge, the clinical significance of plasma mtDNA content in lung cancer remains unknown. Thus, the current study explored the diagnostic and prognostic value of plasma mtDNA quantification in patients with lung cancer. Plasma mtDNA copy numbers of patients with lung cancer (n=128) and healthy individuals (n=107) were quantified by quantitative polymerase chain reaction. Plasma mtDNA co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…Increase of cf-MtDNA has been associated with COPD and, with some contradictory reports, lung cancer (Chen et al, 2018;Hou et al, 2019;Zhang et al, 2020). Results from our study show that the levels of cf-MtDNA in patients with COPD and NSCLC were significantly higher than that in the controls.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Increase of cf-MtDNA has been associated with COPD and, with some contradictory reports, lung cancer (Chen et al, 2018;Hou et al, 2019;Zhang et al, 2020). Results from our study show that the levels of cf-MtDNA in patients with COPD and NSCLC were significantly higher than that in the controls.…”
Section: Discussionsupporting
confidence: 42%
“…However, contradictory findings have been reported. For example, cf-MtDNA copy numbers in blood plasma were lower in patients with lung cancer than that in controls (Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
“…A study suggested that mtDNA content analysis from peripheral blood could serve as a noninvasive biomarker and predictor for hepatocellular carcinoma risk in patients with hepatitis C [152]. Supported by other authors, their study used plasma and found it as a promising complementary sample alongside tissue specimens that served as a predictor for diagnosis and prognosis of lung cancer [154]. Several studies conducted in head and neck cancer areas showed significantly higher cf-mtDNA levels in cancer patients to be compared with control samples [155][156][157].…”
Section: Circulatingmentioning
confidence: 98%
“…Moreover, the number of mtDNA copies have been correlated with different types of cancer. The decrease is reported for breast, liver, lung, and kidney cancers, while in prostate and head and neck cancers, excessive mtDNA copies are observed [199][200][201]. At the same time, cancer cell's mitochondria are considered as therapeutic targets, which may be a feature of personalized medicine in the future [202].…”
Section: Discussionmentioning
confidence: 99%